The next goal: Euro area banking integration - Ignazio Angeloni (Leibniz Institute for Financial Research SAFE, 2024)
In its first ten years (2014-2023), the banking union was successful in its prudential agenda but failed spectacularly in its underlying objective: establishing a single banking market in the euro area. This goal is now more important than ever, and easier to attain than at any time in the last decade. To make progress, crossborder banks should receive a specific treatment within general banking union legislation. Suggestions are made on how to make such regulatory carve-out effective and legally sound.
Keywords: 330; Banking Union; Single Banking Market; Euro Area